1. New Horizons of Indian Christian Living 2.Cathedrals of Development: 1. A Festschrift in Honour of Prof. Dr. Vadakethala Francis Vineeth CMI 2. A Critique on the Developmental Model of Amartya Sen - Kalluveettil, Paul; George, Siby K (Journal of Dharma, 2009)
1. Saju Chackalackal, ed., New Horizons of Indian Christian Living: A Festschrift in Honour of Prof. Dr. Vadakethala Francis Vineeth CMI, Bengaluru and Coimbatore: Vidyavanam Publications and Preshitha Communications, 2009, pages xii + 932, Rs. 900.00; US 50.00. 2. Roy Varghese Palatty, Cathedrals of Development: A Critique on the Developmental Model of Amartya Sen, Bangalore, India: Christ University Publications, 2009, pages: xxxiv + 227.